2016
DOI: 10.1002/14651858.cd004028.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Valproate for schizophrenia

Abstract: There is limited evidence, based on a number of trials, that the augmentation of antipsychotics with valproate may be effective for overall clinical response, and also for specific symptoms, especially in terms of excitement and aggression. However, this evidence was entirely based on open RCTs. Moreover, valproate was associated with a number of adverse events among which sedation and dizziness appeared significantly more frequently than in the control groups. Further randomised studies which are blinded are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 89 publications
1
59
0
1
Order By: Relevance
“…Antipsychotics affect especially positive symptoms, whereas for negative symptoms and cognitive impairment, they are less effective [3]. Antidepressant (AD) or mood stabilizer (MS) use as adjuvants to antipsychotics has been investigated in treatment for symptoms such as depressive and negative symptoms [4] and aggression [5], but they are rarely recommended in clinical guidelines due to lack of high quality evidence of their efficacy [3,6,7]. Evidence on benefits in clinical trials is mixed which was represented by a recent study reporting that add-on citalopram was associated with reduced levels of negative symptoms but had no impact on depressive symptoms [8].…”
Section: Introductionmentioning
confidence: 99%
“…Antipsychotics affect especially positive symptoms, whereas for negative symptoms and cognitive impairment, they are less effective [3]. Antidepressant (AD) or mood stabilizer (MS) use as adjuvants to antipsychotics has been investigated in treatment for symptoms such as depressive and negative symptoms [4] and aggression [5], but they are rarely recommended in clinical guidelines due to lack of high quality evidence of their efficacy [3,6,7]. Evidence on benefits in clinical trials is mixed which was represented by a recent study reporting that add-on citalopram was associated with reduced levels of negative symptoms but had no impact on depressive symptoms [8].…”
Section: Introductionmentioning
confidence: 99%
“…19 There is some evidence that augmenting antipsychotics with valproate may also be effective, especially when aggression is a feature. 20 Mirtazapine is another augmenting option and is one we actually trialled prior to rechallenge with clozapine as evidence has shown that it may have a positive overall effect on a patient's mental state. 21 Despite numerous augmenting agents having been trialled there is a lack of high quality evidence t o m a k e a n y s p e c i f i c recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no specific recommended pharmacological treatment guideline, several agents including antipsychotics, anticonvulsants, anti‐anxiety, and selective serotonin inhibitors are widely used for the treatment of CBS with variable results . The evidence is limited to support the effectiveness of valproate monotherapy in the treatment of psychosis, and it is typically used as an adjuvant particularly for the symptoms of aggression, excitement, and tardive dyskinesia . Nonetheless, valproate was chosen for this patient due to a more favorable side effect profile compared to carbamazepine, which would also require benzodiazepine administration to maximize its therapeutic effect and thus pose many potential risks due to her geriatric status .…”
Section: Discussionmentioning
confidence: 99%
“…The evidence is limited to support the effectiveness of valproate monotherapy in the treatment of psychosis, and it is typically used as an adjuvant particularly for the symptoms of aggression, excitement, and tardive dyskinesia [17,18]. Nonetheless, valproate was chosen for this patient due to a more favorable side effect profile compared to carbamazepine, which would also require benzodiazepine administration to maximize its therapeutic effect and thus pose many potential risks due to her geriatric status [14,16].…”
Section: Discussionmentioning
confidence: 99%